CLINICAL STUDY OF NY-198 IN INFECTIOUS ENTERITIS - AOKI, TAKAKAZU (CHEMOTHERAPY, 1988)
We evaluated the clinical effect and safety of a new quinoline antibacterial agent, NY-198, in patients with acute infectious enteritis (bacillary dysentery, enteropathogenic Escherichia coli enteritis, Campylobacter enteritis, Salmonella enteritis and other bacterial enteritis) and the corresponding carriers (118 subjects in all). NY-198 was orally administered to the subjects at a daily dose of 600 mg for five days, but to patients with acute Salmonella enteritis and Salmonella-carriers for seven days. Our results are summarized as follows: 1. Clinical efficacy rate of NY-198 In 76 evaluable subjects, the overall efficacy rate of NY-198 was 90.8%, and for 31 with bacillary dysentery, the rate was 100%. In 64 subjects excreting causative organisms, the bacteriological rate was 89.1%, and for 29 of these with Shigella spp., the rate was 100%. 2. Safety of NY-198 Of 106 patients, four had side-effects (3.8%): soft stool, nausea, stomach discomfort and epigastric pain in one case each. The rate of abnomal changes in laboratory findings was 6.4%(5/78 patients). These were eosinophilia, elevation of GOT, GPT, GOT GPT and GOT, LDH, respectively. 3. Clinical value of NY-198 In 75 evaluable subjects, the overall clinical value rate was 85.3%, and for 32 with bacillary dysentery, the rate was 93.8%. The above results show that NY-198 is a useful oral antibiotic for infectious enteritis.